Dichroic Fourier Transform Infrared Spectroscopy Characterization of the β-Sheet Orientation in Spider Silk Films on Silicon Substrates - Hofmaier, Mirjam; Urban, Birgit; Lentz, Sarah; Borkner, Christian B.; Scheibel, Thomas; Fery, Andreas; Mueller, Martin (Journal of Physical Chemistry B, 2021)
Orientation analysis of the β-sheet structure within films of the established recombinant spider silk protein eADF4(C16) was performed using a concept based on dichroic transmission- A nd attenuated total reflection-Fourier transform infrared spectroscopy, lineshape analysis, assignment of amide I components to specific vibration modes, and transition dipole moment directions of β-sheet structures. Based on the experimental dichroic ratio R, the order parameter S of β-sheet structures was calculated with respect to uniaxial orientation. Films of eADF4(C16) were deposited on untexturized (Si) and unidirectionally scratched silicon substrates (Si-sc) and post-treated with MeOH vapor. Freshly cast thin and thick eADF4(C16) films out of hexafluoroisopropanol featured β-sheet contents of ≈6%, which increased to >30% after MeOH post-treatment in dependence of time. Pseudo-first order folding kinetics were obtained, suggesting a transition from an unfolded to a folded state. In MeOH post-treated thin films with diameters in the nanometer range, a significant orientation of β-sheets was obtained regardless of the texturization of the silicon substrate (Si, Si-sc). This was rationalized by dichroic ratios of the amide I component at 1696 cm-1 assigned to the (0, I) mode of antiparallel β-sheet structures, whose transition dipole moment M is located in parallel to both β-sheet plane and chain direction. The calculated high molecular order parameter S ≈ 0.40 suggested vertically (out-of-plane) oriented antiparallel β-sheet stacks with tilt angles of γ≈ 39° to the surface normal. Microscale (thick) films, in contrast, revealed low order parameters S ≈ 0. Scanning force microscopy on thin eADF4 films at silicon substrates showed dewetted polymer film structures rather at the micro-scale. These findings give new insights in the role of the β-sheet crystallite orientation for the mechanical properties of spider silk materials.
CRIS-Team Scopus Importer:2022-04-14